Penerapan SAK EMKM Sektor Pertanian Kabupaten Bogor Menuju Pengembangan Industri 4.0 - Rusmanah, Enok; Ariyanto, Nizam Muhamad (E-Jurnal Akuntansi, 2021)
Micro, Small, and Medium Enterprises (MSMEs) are the main drivers of the economy and dominated by the agricultural sector. However, this sector does not show a significant improvement. The main obstacle is the lack of MSME access to financing due to reliable financial reports. Financial Accounting Standards for MSMEs (SAK EMKM) were prepared to address this challenge. This study motivates to determine the perceptions of MSME of agricultural sector towards SAK EMKM. The study is done in Bogor Regency with farmers as the respondens. Descriptive analysis and Technology Acceptance Model (TAM) by Davis (1989) are combined to explain the perceptions. The results show that SAK EMKM was usefull but did not agree that it was easy to implement. Keywords: UMKM; SAK EMKM; Technology Acceptance Model.